Analisa Ekonomi Atas Hukum Pidana terhadap Penanggulangan Tindak Pidana Korupsi - Dedy Syaputra (Wajah Hukum, 2019)
Life in the community will not be far from economic problems, so even economic problems will become a legal problem if the aspect of fulfilling daily needs suffers. Then criminal problems will arise such as theft, and others. Even on a larger scale can the white collar crime arise. The purpose of this study aims to analyze economics of law, or commonly known as "Economic Analysis of Law" will test systemically how people act against legal incentives and analyze them according to social welfare measures. The method used is a normative juridical approach, which is to find the legal norms and norms for dealing with corruption